2005
DOI: 10.1093/humrep/dei419
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal outcome of 12 021 singleton and 3108 twin births after non-IVF-assisted reproduction: a cohort study

Abstract: Perinatal outcome of pregnancies caused by assisted reproduction technique (ART) is substantially worse when compared with pregnancies following natural conception. We investigated the possible risks of non-IVF ART on perinatal health. We conducted a retrospective cohort study with two exposure groups: a study group of pregnancies after controlled ovarian stimulation (COS), with or without artificial insemination (AI), and a naturally conceived comparison group. We used the data from the regional registry of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
76
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(87 citation statements)
references
References 53 publications
6
76
2
3
Order By: Relevance
“…It is hoped that future epidemiologic studies will address this issue. In the meantime, we agree with others [3,4] that in the absence of standardised protocols for the obstetric management of pregnancies conceived with IVF, it is prudent for such gestations to be regarded as high-risk. …”
supporting
confidence: 82%
“…It is hoped that future epidemiologic studies will address this issue. In the meantime, we agree with others [3,4] that in the absence of standardised protocols for the obstetric management of pregnancies conceived with IVF, it is prudent for such gestations to be regarded as high-risk. …”
supporting
confidence: 82%
“…The use of gonadotrophins for ovarian stimulation is the most important cause of multiple pregnancies in ART patients in the United States, with one-third of multiple pregnancies being caused by non-IVF ovarian stimulation (Ombelet et al 2006). Multiple pregnancies are associated with increased risk of miscarriage, growth retardation and preterm delivery (Fauser et al 2005).…”
Section: Perinatal Outcomesmentioning
confidence: 99%
“…Multiple pregnancies are associated with increased risk of miscarriage, growth retardation and preterm delivery (Fauser et al 2005). However, even singletons are at higher risk of low birthweight, premature birth and perinatal mortality and morbidity in the subfertile population using ART (Schieve et al 2002, Helmerhorst et al 2004, Jackson et al 2004, Kapiteijn et al 2006, Ombelet et al 2006. Mouse studies are concordant, as the mean weight of live foetuses was shown to be significantly lower for foetuses obtained from superovulated recipients, compared to that of those obtained from control recipients (Ertzeid & Storeng 2001).…”
Section: Perinatal Outcomesmentioning
confidence: 99%
“…Statistics show that the perinatal outcome of pregnancies after such treatments is substantially less successful in comparison with those following natural conception (Ombelet et al 2006). In Spain delayed childbearing has increased the proportion of births for primiparous women over 35 and the frequency of multiple deliveries, due to the use of assisted reproductive technology (Fuster et al 2008).…”
Section: Introductionmentioning
confidence: 99%